2022
DOI: 10.1038/s41375-022-01678-y
|View full text |Cite|
|
Sign up to set email alerts
|

Translatome proteomics identifies autophagy as a resistance mechanism to on-target FLT3 inhibitors in acute myeloid leukemia

Abstract: Internal tandem duplications (ITD) in the receptor tyrosine kinase FLT3 occur in 25 % of acute myeloid leukemia (AML) patients, drive leukemia progression and confer a poor prognosis. Primary resistance to FLT3 kinase inhibitors (FLT3i) quizartinib, crenolanib and gilteritinib is a frequent clinical challenge and occurs in the absence of identifiable genetic causes. This suggests that adaptive cellular mechanisms mediate primary resistance to on-target FLT3i therapy. Here, we systematically investigated acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Machine learning offers an effective tool for synthesizing and analyzing the amassing omics data to extract prominent features that can be used to develop mechanistic models for hypothesis generation. 49 , 64 As a first step, we look forward to the harmonization of our dataset with other recently published proteomic studies in AML 18 , 23 , 36 , 37 , 39 , 40 to improve prognostication, and better understand the biology of drug response in AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning offers an effective tool for synthesizing and analyzing the amassing omics data to extract prominent features that can be used to develop mechanistic models for hypothesis generation. 49 , 64 As a first step, we look forward to the harmonization of our dataset with other recently published proteomic studies in AML 18 , 23 , 36 , 37 , 39 , 40 to improve prognostication, and better understand the biology of drug response in AML patients.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 , 26 , 27 This motivated the National Cancer Institute (NCI) to create the Clinical Proteomic Tumor Analysis Consortium (CPTAC), in which patient-derived samples were assayed using state-of-the-art mass spectrometry (MS) pipelines to produce proteomic and phosphoproteomic measurements of hundreds of tumors in breast, ovary, kidney, head and neck, endometrium, brain, and other tissues. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Efforts to study the impact of the proteomic signatures on drug response have been previously evaluated in AML cell lines 24 , 36 , 37 and in primary AML patient samples. 18 , 36 , 38 , 39 , 40 In each study, these proteomic measurements demonstrated patterns that were not evident at the genomic or transcriptomic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS-based proteomic approaches mapped the effects of targeted agents on AML cell lines and primary samples and identified key pathways affected by drug treatment ( 33 35 ) and mutational status ( 36 ) or targetable pathways associated with drug resistance ( 37 , 38 ). We previously used computational approaches to integrate proteomic profiling with genomics, transcriptomics, and small-molecule inhibitor sensitivity data sets to create models that recapitulate patient biology, which can be leveraged to prioritize treatment strategies ( 37 , 39 ).…”
Section: The Proteogenomic Landscape Of Solid and Liquid Tumorsmentioning
confidence: 99%
“…Koschade et al. ( 112 ) used quantification of translation changes by proteomics to reveal global attenuation of translation, but an increase in the transcription and synthesis of proteins involved in autophagy, upon FLT3 inhibition. Phosphoproteomics analysis showed an increase in the phosphorylation of proteins related to autophagy and MTOR signaling after pharmacological inhibition of FLT3.…”
Section: Rationalization Of Drug Synergy In Aml Cells Using Proteomic...mentioning
confidence: 99%